Brimonidine purite 0.15% versus dorzolamide 2% each given twice daily to reduce intraocular pressure in subjects with open angle glaucoma or ocular hypertension. Issue 7 (17th June 2004) - Sharpe, E D; Day, D G; Beischel, C J; Rhodes, J S; Stewart, J A; Stewart, W C
Abstract : Background/aims: To evaluate the efficacy of brimonidine purite versus dorzolamide given twice daily in primary open angle glaucoma or ocular hypertensive subjects. Methods: In this double masked, multicentre, prospective, crossover comparison 33 subjects were randomised to brimonidine purite or dorzolamide for the first 4 week treatment period after a 4 week washout. Subjects began the opposite treatment for the second 4 week period after another 4 week washout. Intraocular pressure (IOP) was measured at 08:00 (trough) and 10:00, 18:00, and 20:00 hours after dosing at each baseline and at the end of each treatment period. Results: The baseline diurnal IOP was 22.9 (SD 2.8) for brimonidine purite and 22.2 (SD 2.4) mm Hg for dorzolamide. The trough IOP following 4 weeks of therapy was 21.0 (SD 3.7) for brimonidine purite and 21.0 (SD 3.1) mm Hg for dorzolamide (p = 0.90). The mean diurnal IOP was 19.3 (SD 3.1) for brimonidine purite and 19.8 (SD 2.4) mm Hg for dorzolamide (p = 0.46). Dorzolamide caused more ocular stinging upon instillation (n = 8) than brimonidine purite (n = 1) (p = 0.02). No statistical differences existed between groups for systemic adverse events. Conclusions: This study suggests that brimonidine purite and dorzolamide each given twice daily have similar efficacy in primary open angle glaucoma or ocular hypertensive subjects. However, a trend was observed at 10:00 of greater brimonidine purite efficacy compared with dorzolamide.